N-propargyl aza-Claisen rearrangement in the synthesis of heterocycles. (27th August 2022) - Listratova, Anna V.; Titov, Alexander A.; Obydennik, Arina Y.; Varlamov, Alexey V.
Abstract: Pericyclic reactions present a convenient tool for constructing heterocyclic systems. They make possible to obtain quite complex structures in one step with high yields and stereoselectivity. A special position in this series is assigned to the named reactions of [3, 3]-sigmatropic transformations, including the aza-Claisen one. This rearrangement lately found its brilliant continuation in N -propargyl variant. In the present short review we have tried to provide an overview of the practical application of N -propargyl aza-Claisen rearrangement in the construction of pyrrole, pyridine and medium aza-heterocycle derivatives focusing mainly on literature data on the XXI century. Graphical abstract: Image 1